2022
DOI: 10.3390/ani12202739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dimethylacetamide Concentration on Motility, Quality, Antioxidant Biomarkers, Anti-Freeze Gene Expression, and Fertilizing Ability of Frozen/Thawed Rooster Sperm

Abstract: Sperm cryopreservation is of great importance for the poultry industry but still needs to be optimized. The high susceptibility of poultry sperm to cryodamage leads to low fertility rates after cryopreservation. Therefore, the present study aimed at evaluating the effect of including a cryoprotectant, dimethylacetamide (DMA), in the chicken semen freezing extenders at a final concentration of 3%, 6%, or 9% on the post-thawed sperm motility, quality, antioxidant biomarkers, anti-freeze gene expression, and fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Qi et al [27] reported that RPL29 expression in rooster sperm was substantially downregulated following cryopreservation. However, our study did not show any significant effect on the RPL29 expression using various levels of DMA in postthawed sperm, and these results are in agreement with other studies [2]. On the other hand, Riesco and Robles [56] reported that cryopreservation of Zebrafish genital ridges downregulated most of the gene transcripts and demonstrated that this effect was a result of the freezing/thawing procedure rather than exposure to CPAs themselves.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Qi et al [27] reported that RPL29 expression in rooster sperm was substantially downregulated following cryopreservation. However, our study did not show any significant effect on the RPL29 expression using various levels of DMA in postthawed sperm, and these results are in agreement with other studies [2]. On the other hand, Riesco and Robles [56] reported that cryopreservation of Zebrafish genital ridges downregulated most of the gene transcripts and demonstrated that this effect was a result of the freezing/thawing procedure rather than exposure to CPAs themselves.…”
Section: Discussionsupporting
confidence: 92%
“…Rooster spermatozoa have smaller cytoplasm contents, antioxidants, and mitochondria and higher polyunsaturated fatty acid levels within the plasma membrane than their counterpart in mammals. Thus, rooster spermatozoa are more susceptible to damage throughout the freezing-thawing process [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Despite difficulties, successful cryopreservation protocols have been developed for valuable genetic lines of chickens, turkeys, ducks and geese using glycerol or dimethylacetamide (DMA) as permeating cryoprotectants 6 8 . Optimal cooling rates, straw sizes and thawing rates have been elucidated 4 , 8 , 9 . Non-permeating agents like liposomes, egg yolk or polymers provide additional sperm protection when added to standard glycerol or DMA freezing media 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The previous study analysed the antioxidant biomarkers and the anti-freeze-associated gene expression in the postthawed sperm of rooster (Mehaisen et al 2022). Testes are the site of spermatozoa production, while the epididymis has stored spermatozoa (Hedger 2011).…”
Section: Introductionmentioning
confidence: 99%